Bridging Asia and Africa: Indonesia's Kemitraan Negara Berkembang Scholarship and Educational Diplomacy for SDGs 4 - Sufianissa'adah Sufianissa'adah; Muhammad Fajhriyadi Hastira; Ali Maksum; Albidri Baharil Albi (Institute of Multidisciplinary Research and Community Service, 2026)
This study examines the role of Indonesia’s Developing Countries Partnership Scholarship (KNB) as an instrument of educational diplomacy and soft power in strengthening educational cooperation with partner countries, particularly Pakistan and Malawi, while supporting Sustainable Development Goal (SDG) 4 on quality education. Using a qualitative approach, this study combines documentary research, thematic analysis, media content analysis, and bibliometric mapping to analyze official policy documents, academic literature, and public media narratives related to the implementation of the KNB Scholarship. The findings indicate that the KNB Scholarship not only functions as a financial aid program but also promotes access to education, South-South solidarity, intercultural understanding, and long-term educational cooperation, thereby strengthening Indonesia’s image as a development partner through non-coercive engagement. By strengthening academic collaboration and institutional partnerships with developing countries while supporting SDG 4 through expanded access to quality higher education, this program also supports the internationalization of Indonesian higher education. The program’s effectiveness also depends on adequate institutional support, including language assistance, academic adaptation, inter-institutional coordination, and systematic program evaluation. Overall, the findings suggest that the KNB Scholarship is not merely a scholarship program but also a strategic instrument of educational diplomacy that advances Indonesia’s soft power and strengthens sustainable educational cooperation. By integrating soft power, the internationalization of higher education, and a human capital perspective into a single analytical framework, this study contributes to the literature on educational diplomacy. It provides policy insights to improve institutional support mechanisms. For future research, it is recommended to examine the long-term outcomes of the KNB Scholarship by conducting alumni tracking and comparative analyses involving more partner countries. Keywords: Educational Diplomacy, KNB Scholarship, Soft Power, Higher Education Internationalization, South-South Cooperation, SDG 4